Mask shortage during epidemics and pandemics: a scoping review of interventions to overcome limited supply. Issue 11 (27th November 2020) - Kirubarajan, Abirami; Khan, Shawn; Got, Tiffany; Yau, Matthew; Bryan, Jennifer M; Friedman, Steven Marc
Abstract : Objective: To characterise published evidence regarding preclinical and clinical interventions to overcome mask shortages during epidemics and pandemics. Design: Systematic scoping review. Settings: All healthcare settings relevant to epidemics and pandemics. Search strategy: English peer-reviewed studies published from January 1995 to June 2020 were included. Literature was identified using four databases (Medline-OVID, EMBASE, CINAHL, Cochrane Library), forwards-and-backwards searching through Scopus and an extensive grey literature search. Assessment of study eligibility, data extraction and evidence appraisal were performed in duplicate by two independent reviewers. Results: Of the 11 220 database citations, a total of 47 articles were included. These studies encompassed six broad categories of conservation strategies: decontamination, reusability of disposable masks and/or extended wear, layering, reusable respirators, non-traditional replacements or modifications and stockpiled masks. Promising strategies for mask conservation in the context of pandemics and epidemics include use of stockpiled masks, extended wear of disposable masks and decontamination. Conclusion: There are promising strategies for overcoming face mask shortages during epidemics and pandemics. Further research specific to practical considerations is required before implementation during the COVID-19 pandemic.